Mathematical Communication and Social Skills of The Students through Pair Check Type Cooperative Learning Models - Farokah, Esti; Winarso, Widodo (Yayasan Sukma, 2021)
Lack of students 'social skills makes students' mathematics learning less optimal. The learning model that is carried out is often not maximizing the learning process-oriented towards mathematical communication skills. This makes the teacher strive for a learning method or strategy to foster students' social skills and mathematical communication skills. The Pair Check method is one of the learning methods expected to train and improve students' social skills and mathematical communication skills. The subjects of this study were 24 students of class VII B MTs Riyadlul Ulum Bendungan. The results showed that: (1) students social skills had a percentage of 74.05% with the